Effect of Time to Sowing on the Performance of Five High-Yielding Wheat Varieties - Verma, U K; Verma, B N; Singh, S P; Pandit, S (Annals of Arid Zone, 2016)
The paper embodies a study of different dates of sowing on the performance of five high-yielding wheat varieties. The results indicate that wheat sown on 1st December gave the highest grain yield, and amongst the varieties, Kalyan Sona and Sonalika were better than others.